Effects of annealing temperature and template diameter on the microstructures of BiFeO3 nanowires. (7th December 2016) - Sun, Fei; Fu, Chunlin; Gao, Rongli; Zou, Jihua
ABSTRACT: Bismuth ferrite (BFO) nanowires were prepared by anodic aluminum oxide templates with different diameters and at different annealing temperatures. It is found that the annealing temperature and the template diameter affect crystal structure and surface topography of BFO nanowires. X-ray diffraction results show that all nanowires correspond to rhombohedral distorted perovskite structure. It can be observed from scanning electron microscope that the diameters of nanowires are in the range of 80 to 100 nm. And there are a large number of nanowires lining regularly. The nanowires of 'Y' model are discovered by transmission electron microscopy. SAED image reveals BFO nanowires coincide with the polycrystalline nature.